Bard and Pic's syndrome of lithiasic etiology - Pérez Billi, Luis; Praderi, José; Lago, Fernando; di Donna, Bruno; Bermúdez, Jorge; Castiglioni, Dinorah (Cirugía del Uruguay, 1984)
Analysis of 8 patients with jaundice and palpable gallbladder (Bard & Pic's sign), of lithiasic etiology. Described are physiopathological mechanisms that account for this association, pointing out the necessity of a correct study pre and intra-operative ti:, prevent gross error in the surgical treatment.